Chitosan-gelatin-based microgel for sustained drug delivery. Issue 5 (23rd March 2016) - Wang, K.; Lin, S.; Nune, K. C.; Misra, R. D. K.
Abstract: We describe here the proof-of-concept of synthesizing microgels via cross-linking of chitosan and gelatin with succinimide-end polyethylene glycol (PEG). The introduction of PEG provided thermo-responsiveness to microgels, and the size of microgels significantly changed with increasing temperature. Furthermore, the microgel was biocompatible as confirmed in vitro by MTT assay with NIH 3T3 fibroblast and degradable. Chitosan-based microgels exhibited strong affinity to hydrophobic drug and prolonged release of folic acid was observed at physiological temperature with varying pH. The proposed cost-effective injectable microgels have the potential to serve as the delivery vehicle of hydrophobic bioactive molecules.